2017
DOI: 10.1186/s12885-017-3220-x
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of the preoperative c-reactive protein/albumin ratio in ovarian cancer

Abstract: Background: Inflammation plays an important role in the pathogenesis of ovarian cancer. This study sought to investigate the association between the preoperative c-reactive protein/albumin ratio (CRP/Alb) and oncological outcomes in ovarian cancer patients. Methods: Two hundred patients with histologically verified ovarian cancer between June 2006 and July 2012 were retrospectively reviewed. Overall survival was evaluated by the Kaplan-Meier method and log-rank test. The significance of risk factors for overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 43 publications
3
103
0
Order By: Relevance
“…Among them, systemic inflammatory response and nutritional status are two important contributors [21] . Evidences showed that CAR was an important inflammation-based prognostic indicator that associated with various cancer survival outcomes [22,23] . In the present study, we found that CAR was an independent prognostic indicator in patients with gastric cancer, which was in agreement with previous studies [12,13,20] .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, systemic inflammatory response and nutritional status are two important contributors [21] . Evidences showed that CAR was an important inflammation-based prognostic indicator that associated with various cancer survival outcomes [22,23] . In the present study, we found that CAR was an independent prognostic indicator in patients with gastric cancer, which was in agreement with previous studies [12,13,20] .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 11 articles were selected for full review, as shown in Figure 1. Six articles were excluded for various reasons, leading to the final inclusion of five articles for study [10][11][12][13]16]. Table 1 summarizes the characteristics of the five included studies.…”
Section: Selection Processmentioning
confidence: 99%
“…However, evidence of the significance of the PNI in OC is controversial. A retrospective study by Feng et al [10] on 875 OC patients revealed null results between preoperative PNI and overall survival (OS) of OC, in contrast to other studies that showed a significant association [11][12][13]. Interestingly, a systematic review and meta-analysis in 2019 by Wang et al [14] showed significant association of the PNI with the prognosis of patients with gynecological cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CRP/albumin ratio has been investigated in various solid tumors, including hepatocellular carcinoma, non‐small cell lung cancer, ovarian, and pancreatic adenocarcinomas . In these studies, high levels of acute phase proteins as expressed by an elevated ratio (high CRP and/or low albumin) were consistently associated with adverse outcome.…”
Section: Introductionmentioning
confidence: 99%